Developing Culture-Based English Language Assessment Instrument for Second Semester of Grade Seven of Junior High School in Buleleng Sub-District to Support the Implementation of Curriculum 2013 - Ida Ayu U Wasundari; Ni Komang Arie Suwastini; I Gede Batan (Lingua Scientia, 2016)
This research aimed at developing culture-based English language assessment instrument for the second semester of grade seven of junior high school in Buleleng Subdistrict to support the implementation of Curriculum 2013. This research was categorized as research and development. Research and development model which was used in this research proposed by Peffers et.al (2007). The suitable English assessment for the second semester of grade seven of junior high school was English assessment with integrated Balinese culture in order to support the development of character building. The steps of developing this English assessment instrument included assessment goal analysis, assessment standard analysis, syllabus analysis, learning source analysis, designing blue print, developing assessment, expert judgment, and revision. This research produced English assessment instrument which assessed students’ affective, cognitive, and psychomotor domains. The reliability and quality of the developed assessment instrument were found out by giving expert judgment form to the experts of assessment and English language teaching. The scores which were given by the two experts were 650 from the first expert and 802 from the second expert. Based on those scores, the quality of the developed English assessment instrument was categorized as excellent. The reliability of the data was categorized as excellent in which the score of Alpha Cronbach’s coefficient was 0.9. It means that the developed culturebased English assessment instrument was suitable to be used in teaching and learning process that implements Curriculum 2013 in Buleleng Sub-district.